Investigations of the guide tube wear in Ringhals pressure water reactors - Olofsson, Peter (My University, 2011)
Guide tubes in Pressure Water Reactors (PWR) are subjected to wear as a result from the contact with control rods. This specific wear has been observed at several international nuclear power plants. The wear can cause problems with the drop time, interference with the Rod Cluster Control Assembly (RCCA) and stuck control rods. At Ringhals, guide tube inspections have been performed for unit 2 and 3 in 2006, unit 4 in 2007 and again in unit 3 in 2010. The results from these inspections are studied and analyzed in this report. It also includes a search for causes and patterns of the guide tube wear. The current status of the guide tubes at Ring- hals is evaluated. The wear is then quantified and compared with wear criterions, defined by companies and organizations in the business. According to the prede- fined criterions, wear of the guide tubes at Ringhals are relatively moderate. Data from the inspections have some sources of errors and further improvement of the methodology is recommended.
Keywords: Övrig teknisk fysik; Energi; Other engineering physics; Energy